2013
DOI: 10.3109/00365548.2013.765589
|View full text |Cite
|
Sign up to set email alerts
|

The implications of the presence of osteomyelitis on outcomes of infected diabetic foot wounds

Abstract: The presence of osteomyelitis negatively affects both the treatment and outcome of diabetic foot infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 24 publications
1
70
0
2
Order By: Relevance
“…Duration of antibiotic treatment, length of hospital stay, the duration of infection before initiation of treatment were longer in the 121 cases with osteomyelitis in our study compared to other patients. Mutluoğlu et al compared patients with and without osteomyelitis; and found that length of hospital stay and antibiotic treatment, time before initiation of treatment and wound healing times were longer and more surgical interventions were required for patients with osteomyelitis [20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Duration of antibiotic treatment, length of hospital stay, the duration of infection before initiation of treatment were longer in the 121 cases with osteomyelitis in our study compared to other patients. Mutluoğlu et al compared patients with and without osteomyelitis; and found that length of hospital stay and antibiotic treatment, time before initiation of treatment and wound healing times were longer and more surgical interventions were required for patients with osteomyelitis [20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a study of hospitalized patients with DFIs, minor amputation was significantly higher in patients with osteomyelitis than in patients with SSTIs (59.4% vs 13.8%). 10 Prior amputation is associated with increased risk of hospitalization. 11 Minor amputations alter the architecture of the foot and make the patient prone to further ulceration.…”
Section: Introductionmentioning
confidence: 99%
“…A closer look at Table 1 in Santema et al (1) shows that patients in the standard care arm had significantly lower grade wounds (in total, 42% patients had Wagner grade III and IV wounds in the standard care arm vs. 55% in the HBOT arm). The fact that wounds with Wagner grade III and IV have a very high likelihood of osteomyelitis and that patients with osteomyelitis almost always suffer amputation (3) causes a bias toward worse outcomes in the HBOT arm.…”
mentioning
confidence: 99%